Economic Aspects of Unit Operation of Oil Pools - Joseph E. Pogue (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1930)
THERE are two methods employed in the development of oil pools. The older and dominant method is one in which the primary object is the protection of the underground deposit from drainage through competing wells, and considerations of efficiency of extraction and cost of production are subordinated thereto. The newer and less prevalent method is one in which maximum efficiency and minimum cost are the first objectives and developments to these ends may proceed undisturbed by the exigencies of competitive drainage. The second method has developed mainly in pools under single ownership and the term "unit operation" has come to be applied to this procedure. A single ownership, however, is not essential to the method, for unity of operation may be achieved by agreement under split ownership, or even by a concert of enlightened purpose. There are examples of unit operation where neither the ownership nor the management is a unit, but merely where unity of procedure has been attained, as is the case of the Yates pool. .Throughout this paper unit operation is used in its broad sense without implying sole ownership or single management, although unit operation is more conveniently attained where these conditions are present.